2021
DOI: 10.3126/mjsbh.v20i1.28777
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction among Nurses Working in a Tertiary Level Government Hospital

Abstract: Introduction: Job satisfaction refers to the employees having a feeling of job stability, career growth and a comfortable work life balance which implies that the employee is having satisfaction at job and the individual’s expectations are met. Job satisfaction is one of the most important factors that determine efficiency and productivity of human resources. It is vital to increase nurse’s job satisfaction to improve patients care quality and ensure adequate nursing workforce which helps in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…A study conducted among the nurses in a tertiary level of Government hospital found that less than 50% of respondents were satisfied with their job and there was a statistical association between level of job satisfaction and marital status, professional qualification, and work experience. Where as the current study shows that more than 50% nurses were satisfied with their current job and there is no any statistical association between job satisfaction and marital status, professional qualification and work experience so this study does not support the current study (Ajanta Singh1, 2021).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A study conducted among the nurses in a tertiary level of Government hospital found that less than 50% of respondents were satisfied with their job and there was a statistical association between level of job satisfaction and marital status, professional qualification, and work experience. Where as the current study shows that more than 50% nurses were satisfied with their current job and there is no any statistical association between job satisfaction and marital status, professional qualification and work experience so this study does not support the current study (Ajanta Singh1, 2021).…”
Section: Discussioncontrasting
confidence: 67%
“…Study showed that nearly half of the nurses were satisfied with their job. The most satisfying factor is the work itself whereas the least satisfying factor is the recognition and reward given them followed by participation in decision making (Ajanta Singh1, 2021). A study found that 60.8% of nurses were satisfied with their job (Firew Ayalew, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In a similar vein, another study discovered that organizational and administrative policies have a significant role in forecasting levels of work satisfaction [22]. Similarly, a prior study, showed that nurses job satisfaction was influenced by several factors, including interpersonal connections, physical infrastructure, working environment, financial and non- [23]. A separate investigation, revealed that nurses were motivated to remain employed at public teaching hospitals due to the presence of financial incentives and fringe benefits.…”
Section: Introductionmentioning
confidence: 82%
“…Previous research has dedicated significant attention to the examination of work-family conflict [17][18][19] and the role of social support [20]. A substantial body of nursing literature in Nepal has conducted comprehensive investigations on the topic of work satisfaction [21][22][23][24][25][26][27]. For example, a research conducted by Shrestha et al [21], showed that individuals who viewed themselves as significant assets to the healthcare system reported greater levels of work satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as work overload, unclear job descriptions, staff problems, shift coverage, low pay, and limited promotion opportunities have been frequently linked to the increased susceptibility of nurses to experience job dissatisfaction and diminished commitment (Bit-Lian, Woei-Ling & Shuhaimi, 2022). While nurses reported overall satisfaction with their nursing practice, they expressed dissatisfaction in other aspects, such as their involvement in decision-making, recognition and reward, and limited career advancement opportunities (Bit-Lian, Woei-Ling & Shuhaimi, 2022;Singh, Chakradhar & Joshi, 2021). Ee, E (2018) reported that 62% of the study's respondents experienced job dissatisfaction, primarily poor communication with colleagues.…”
Section: Introductionmentioning
confidence: 99%